2019
DOI: 10.1111/vde.12755
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro antibacterial activity of the anthelmintic drug oxyclozanide against common small animal bacterial pathogens

Abstract: Background Repurposing existing drugs is one approach to address the growing concerns of multi‐drug resistant bacterial pathogens in veterinary medicine. Oxyclozanide is in the anthelmintic drug class salicylanilide, which has been used primarily as a treatment and preventative for Fasciola hepatica in ruminants. The antimicrobial activity of oxyclozanide has been studied in human medicine; its activity against common small animal bacterial pathogens such as Staphylococcus pseudintermedius has yet to be determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…To date, evidence on the efficacy of bacteriophages or lysins in the management of MRSP infections (prevention or treatment) has not been published, nor are there approved products containing bacteriophages or lysins (Moodley et al, 2019;van Duijkeren et al, 2011). Other drugs, such as oxyclozanide, have demonstrated in vitro antibacterial activity against MRSP (Levinson et al, 2019).…”
Section: Non-antimicrobial Control Optionsmentioning
confidence: 99%
“…To date, evidence on the efficacy of bacteriophages or lysins in the management of MRSP infections (prevention or treatment) has not been published, nor are there approved products containing bacteriophages or lysins (Moodley et al, 2019;van Duijkeren et al, 2011). Other drugs, such as oxyclozanide, have demonstrated in vitro antibacterial activity against MRSP (Levinson et al, 2019).…”
Section: Non-antimicrobial Control Optionsmentioning
confidence: 99%
“…Furthermore, the MPC of halicin for E. coli ATCC 25922, S. aureus ATCC 29213, and APP S6 indicated a relatively narrow MSW for halicin against these strains ( Table 3 ), suggesting a reduced likelihood of resistance development. Levinson et al [ 50 ] reported that the MPC and MSW of oxyclozanide against S. aureus were 16 µg/mL and 1–16 µg/mL, respectively. Pan et al [ 51 ] reported that the MPC of fosfomycin against E. coli ATCC 25922 is 57.6 µg/mL, and the MSW ranges from 2 to 57.6 µg/mL.…”
Section: Resultsmentioning
confidence: 99%